Regulation of beta-adrenergic receptors by "permissive" hormones: glucocorticoids increase steady-state levels of receptor mRNA. - Hadcock, J R (1988)
Incubation of DDT1 MF-2 hamster vas deferens cells with glucocorticoids results in a marked increase in beta-adrenergic receptor (beta AR) number. The increase in receptor number was visualized by indirect immunofluorescence with antiserum specific for the beta AR and was verified by radioligand binding. The steady-state levels of beta AR mRNA were quantified in untreated (control) and glucocorticoid-treated cells by DNA-excess solution hybridization using a single-stranded probe corresponding to nucleotides +12 to 182 of the hamster beta 2AR cDNA coding region. The steady-state level increased from 0.37 pg of beta AR mRNA per microgram of total cellular RNA in untreated cells to 1.05 pg of beta AR mRNA per microgram of RNA in cells treated with dexamethasone (500 nM) for 2-4 hr. After this sharp transient peak, the steady-state level of receptor mRNA declined by 6 hr to a level approximately twice that of the untreated cells. Half-maximal effects were achieved at 20-40 nM dexamethasone. Testosterone (500 nM) and 17 beta-estradiol (500 nM), in contrast, did not alter the steady-state levels of beta AR mRNA. Actinomycin D, a potent inhibitor of transcription, abolished the dexamethasone-induced increase in beta AR mRNA, suggesting that the permissive hormone effect was exerted on gene transcription. The half-life of the receptor mRNA measured in the presence of actinomycin D was found to be 12 hr in both the untreated and the dexamethasone-treated cells. These studies provide a molecular explanation for the well-known regulation of GTP-binding protein (G-protein)-linked cell-surface receptors by permissive hormones.